A propensity matched case–control study comparing efficacy, safety and costs of the subcutaneous vs. transvenous implantable cardioverter defibrillator. (1st February 2017) - Honarbakhsh, S.; Providencia, R.; Srinivasan, N.; Ahsan, S.; Lowe, M.; Rowland, E.; Hunter, RJ; Finlay, M.; Segal, O.; Earley, MJ; Chow, A.; Schilling, RJ; et al.
Abstract: Background: Subcutaneous implantable cardioverter defibrillators (S-ICD) have become more widely available. However, comparisons with conventional transvenous ICDs (TV-ICD) are scarce. Methods: We conducted a propensity matched case–control study including all patients that underwent S-ICD implantation over a five-year period in a single tertiary centre. Controls consisted of all TV-ICD implant patients over a contemporary time period excluding those with pacing indication, biventricular pacemakers and those with sustained monomorphic ventricular tachycardia requiring anti-tachycardia pacing. Data was collected on device-related complications and mortality rates. A cost efficacy analysis was performed. Results: Sixty-nine S-ICD cases were propensity matched to 69 TV-ICD controls. During a mean follow-up of 31 ± 19 (S-ICD) and 32 ± 21 months (TV-ICD; p = 0.88) there was a higher rate of device-related complications in the TV-ICD group predominantly accounted for by lead failures (n = 20, 29% vs. n = 6, 9%; p = 0.004). The total mean cost for each group, including the complication-related costs was £9967 ± 4511 ($13, 639 ± 6173) and £12, 601 ± 1786 ($17, 243 ± 2444) in the TV-ICD and S-ICD groups respectively (p = 0.0001). Even though more expensive S-ICD was associated with a relative risk reduction of device-related complication of 70% with a HR of 0.30 (95%CI 0.12–0.76; p = 0.01) compared to TV-ICDs. Conclusions: TV-ICDs are associated with increased device-related complication rates compared to a propensity matched S-ICD group during a similar follow-up period. Despite the existing significant difference in unit cost of the S-ICD, overall S-ICD costs may be mitigated versus TV-ICDs over a longer follow-up period.